Design of Digital Control System for Line Following Robot - Abdulhamid, Mohamad (Indonesian Applied Physics Letters, 2024)
Design of mobile robots has become an increasingly growing trend in the technology of modern times. They are very attractive engineering systems, not only because of many interesting theoretical aspects concerning kinematics, intelligent behavior and autonomy, but also because of applicability in many human activities. A typical example is the line following robot (LFR). In order for a LFR to function effectively, it must demonstrate excellent line tracking control. This is achieved by having accurate and responsive control algorithms as well as high precision color sensor systems. This paper proposes a system to show that good line tracking performance can be achieved with moderately simple digital control algorithms. The platform used is a differentially driven wheeled robot constructed using the Lego Mindstorms components. The simulation models are presented and analyzed using MATLAB Simulink . The main programming environment is the EV3 Software.